PENGARUH LITERASI KEUANGAN, MOTIVASI, PERSEPSI KEMUDAHAN, RISIKO INVESTASI TERHADAP MINAT BERINVESTASI PADA PASAR MODAL SYARIAH: (STUDI KASUS PADA MAHASISWA PRODI MANAJEMEN KEUANGAN SYARIAH DI JAWA TIMUR) - Viki Rahmat Diansyah,; Amalia Nuril Hidayati, (Juremi: Jurnal Riset Ekonomi, 2022)
This study aims to examine the effect of financial literacy, financial motivation, perceived convenience, and investment risk on students' interest in investing in the Islamic capital market. The approach in this study uses a quantitative approach with associative type. The total population in the study amounted to 1185 consisting of MKS UIN Sayyid Ali Rahmatullah Tulungagung students with 1057 students and MKS UNZAH Genggong Probolinggo with 128 students. 17 students from the MKS department of UNZAH Genggong Probolinggo were taken using a purposive sampling technique with the criteria for MKS students who had received Islamic capital market courses, and were calculated using the Slovin formula with an error rate of 10% in determining sample quality and the results were 97.1% or 97. The author determines 100 respondents to avoid errors in filling out the questionnaire in collecting research data. Data collection techniques in this study used a questionnaire questionnaire. The data that has been collected is then tested using SPPS, namely testing several tests which include, validity test, reliability test, data normality test, multicollinearity test, heteroscedasticity test, T test, and F test. The results showed that the variables of financial literacy, investment motivation, and the perception of convenience has a significant positive effect on investment interest in the Islamic capital market. Then, investment risk has a negative effect on student investment interest because the higher the investment risk, the lower the student's interest in investing.